2021
DOI: 10.2478/jvetres-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the morphometry of heads of normal sperm and sperm with the Dag defect in the semen of Duroc boars

Abstract: Introduction The Dag defect is one of the primary morphological defects in sperm correlating with reduced fertility. This defect is found in the spermatozoa of many livestock species. The aim of the study was to assess the morphometry of the heads of normal sperm and sperm with the Dag defect in the semen of Duroc breeding boars. Material and Methods Sperm morphology was examined in ten ejaculates each from 12 Duroc boars. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
3
2
Order By: Relevance
“…The same study did not find differences in mean regularity and elongation scores between different breeds which is supported by the findings of the current study where no differences in mean values were found between the study breeds. Ellipticity indicates the degree to which sperm heads are oval or conical (Banaszewska and Andraszek 2021). Its mean score in this study was generally similar to an earlier reported value (2.0) for Duroc and Risco boars (Saravia et al 2007).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The same study did not find differences in mean regularity and elongation scores between different breeds which is supported by the findings of the current study where no differences in mean values were found between the study breeds. Ellipticity indicates the degree to which sperm heads are oval or conical (Banaszewska and Andraszek 2021). Its mean score in this study was generally similar to an earlier reported value (2.0) for Duroc and Risco boars (Saravia et al 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The current mean perimeter values were ca. 2µm lower than the earlier reported figures (Banaszewska and Andraszek 2021). The above subtle but important variations between our study and the previous ones may be attributed to differences in breeds studied, age, sperm concentration, incubation temperature, storage time, and staining technique (Saravia et al 2007;Czubaszek et al 2019;Szablicka et al 2022).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We determined that the beginning of bending of the flagellum was observed in the period of passage of spermatozoids through the epididymis, which is characteristic of detachment of the cytoplasmic drop. Such type of abnormalities as residual cytoplasmatic drop in the distal section of spermatozoids is considered to cause no decrease in fertility, though it may be a reason for the so-called "Dag defect" (Saravia et al, 2007;Banaszewska & Andraszek, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By applying ASTMA technology and multivariate procedures such as cluster analysis, it was observed that boar semen samples contained spermatozoa subpopulations of different morphometric characteristics that are not detectable by conventional subjective methods [ 22 , 23 ]. Morphometric results can vary depending on internal factors such as individual variability, species, breed, sexual maturity and age [ 23 , 24 , 25 ], and external factors including environmental factors, sample preparation and the morphometric analysis of semen [ 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%